Using an Embedded Mixed Methods Design to Assess and Improve Intervention Acceptability of an Equity-Focused Intervention: A Methodological Demonstration. (May 2023) - Bastable, Eoin; Meng, Paul; Falcon, Sarah Fairbanks; McIntosh, Kent
Educators have shown reluctance to implement interventions aimed at improving racial equity in school disciplinary practice. Mixed methods were applied to assess and improve the acceptability of a new intervention designed to reduce racial disparities in school discipline. A descriptive concurrent parallel design was used to assess U.S. educators' perceptions of the acceptability of the intervention. Quantitative findings from professional development workshops introducing the intervention to 118 educators were corroborated with qualitative findings from a separate sample of 4 teachers who implemented it in their classrooms. Quantitative findings indicated that the intervention was acceptable to a broad range of potential implementers, and qualitative findings were used to modify the intervention to further improve its utility. The strengths, limitations, and implications of embedding mixed methods approaches to assess school-based interventions are also discussed.